THE ROLE OF EXTRACURRICULAR ACTIVITIES IN DEVELOPING THE SKILLS OF THE TWENTY-FIRST CENTURY FOR STUDENTS IN LIGHT OF KSA 2030 VISION - Dr. Sherin Hassan Mabrouk , Dr.Rania Mohammed Abdul Jawad , Dr. Mona abdelmoneim abdelmabood , Ms Lamyaa Mohamed Badr Ali Marzouk (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify the role of extracurricular activities in developing the skills of the twenty-first century in the light of the Kingdom’s 2030 vision for female students of the preparatory year at Imam Abdul Rahman bin Faisal University. The second year of the academic year 2018-2019, the importance of research and the need for it in response to the directions of the Kingdom of Saudi Arabia and to achieve the vision of 2030 in the inclusion of the skills of the twenty-first century within the programs of preparing university students, the scarcity of research that dealt with the inclusion of skills of the twenty-first century within the programs of extracurricular activities of university students, and Participation in the analysis of extracurricular activities, one of the effective participations in the process of developing extracurricular activities carried out within the university, so the importance of the study stands out in benefiting from its results and from the recommendations that, God willing, will contribute to improvement and development. The most important results were the effectiveness of the questionnaire in measuring the role of extracurricular activities in developing the skills of the twenty-first century in the light of the Kingdom’s 2030 vision for students of the preparatory year at Imam Abdul Rahman bin Faisal University. Extracurricular activities play a positive role in providing students with some of the skills of the twenty-first century, there are deficiencies in addressing Some skills of the twenty-first century through extracurricular activities, in the light of the findings of the researchers recommend Taking advantage of the results of the current study and the suggested vision by the researchers in developing extracurricular activities in the Kingdom in the light of the skills of the twenty-first century, and merging the skills of the twenty-first century within the goals of extracurricular activities plans, 3 developing extracurricular activities programs for students in line with the requirements and developments of the current era, and the development of extracurricular activities For students to acquire these skills and creativity in them, to establish a calendar plan for the performance of university activity committee officials, and for the good professional .preparation of university activity supervisors